Resource allocation and metabolism: the search for governing principles. (October 2018) - Basan, Markus
Abstract : Elucidating strategies of resource allocation and metabolism is crucial for a better understanding of microbial phenotypes. In particular, uncovering the governing principles underlying these processes would be a crucial step for achieving a central aim of systems microbiology, which is to quantitatively predict phenotypes of microbial cells or entire populations in diverse conditions. Here, some of the key concepts for understanding cellular resource allocation and metabolism that have been suggested over the past years are reviewed. In particular, recent experimental studies that have shown how phenotypic patterns from orthogonal genetic and environmental perturbations can help to differentiate between competing hypotheses and their respective predictions are discussed. Phenomenological models have proven to be a valuable addition to genome-scale models, capable of making quantitative predictions with only few parameters and having aided the identification of molecular mechanisms.